Nager's acrofacial dysostosis - Arpita Rai; Kirty R Nandimath; Atul P Sattur; Venkatesh G Naikmasur (Wolters Kluwer Medknow Publications, 2013)
Acrofacial dysostosis (AFD) is a generic name for a variety of different but possibly related genetic disorders that result in craniofacial and limb malformations and are, therefore, categorized under oroacral disorders. Several different variants have been identified and Nager preaxial AFD represents the association of mandibulofacial dysostosis with limb anomalies, particularly hypoplasia of the radial aspect of the hand. This report features a case of a 21-year-old male presenting with malar hypoplasia, downward sloping palpebral fissures, high-arched palate, radioulnar synostosis, hypoplasia of the right thumb and lower limb anomalies.